COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN KAMPUNG WISATA PRAIIJING DI DESA TEBARA KECAMATAN KOTA WAIKABU-BAK KABUPATEN SUMBA BARAT - Yoseph Molla; Tjahya Supriatna; Layla Kurniawati (Institut Pemerintahan Dalam Negeri, 2021)
The purpose of this study is to observe the process and factors of Collaborative Governance in the management of Praiijing tourism village in Tebara village, Waikabubak city district. The qualitative descriptive method with the Collaborative Governance theory approach from Ansell and Gash (2007) is used as theoretically based in this study. The techniques of data collection are through interviews, documentation, and observations. This is due to the influence of internal and external factors in the management of Praiijing tourism village in the field such as cultural factors, institutional management, budgets, geographical location, community, human resources, cultural attractions, structuring, local government policies, regional accessibility, technology, the competitiveness of similar tourism objects and cultural value shifts that will be challenged in the future.